The palaeomagnetism and magnetic fabric of cave sediments from Gronligrotta and Jordbrugrotta, Norway - Noel, Mark; St Pierre, Shirley (Geophysical Journal International, 1984)
Twenty-four oriented specimens of laminated clay were obtained from vertical sections in two caves in northern Norway. Studies of the magnetic remanence and susceptibility anisotropy show that the magnetization is depositional in origin and due to magnetite. The palaeomagnetic record in one section is correlated with results from a Swiss lake sediment core to suggest an age of 9600–6800 yr bp for the cave clay. It is shown that the susceptibility lineation produced on gently sloping surfaces was predominantly controlled by gravity and cannot therefore be used directly to estimate the palaeoflow or palaeofield directions.